Association between Healthy Eating Index-2020, alternative Mediterranean Diet scores, and gastrointestinal cancer risk in NHANES 2005–2018 - Weijie Wang; Yu Chang; Geng Chen (Scientific Reports)
Abstract Diet quality is closely related to the occurrence of gastrointestinal (GI) cancers; however, few studies have investigated the association between the Healthy Eating Index (HEI-2020) and the alternative Mediterranean diet (aMED) scores and GI (GI) cancers. This study aims to assess the association between HEI-2020, aMED scores and GI cancers. Information from a total of 26,320 participants was included in the National Health and Nutrition Examination Survey (NHANES). In our sub-analysis, we focused on participants with complete dietary and health data, specifically assessing the relationship between diet quality and GI cancers outcomes. The 24-hour recall questionnaire was used to collect and assess the participants’ average dietary intake. Diagnoses of GI cancers were based on self-reported medical history confirmed through physician interviews or linked cancer registry data, ensuring diagnostic reliability. Logistic regression models, restricted cubic splines (RCS), subgroup analysis, and interaction methods were employed to fully evaluate the associations between HEI-2020, aMED scores, and GI cancers. Mediation analysis was also conducted to identify potential mediators of this relationship. Even after fully adjusting for potential confounders, participants with high adherence to the HEI-2020-2020 and aMED scores were significantly associated with a reduced risk of GI cancers. Compared to the lowest tertile of HEI-2020, participants in the highest tertile had a 30% reduced risk of GI cancers (OR 0.70, 95% CI 0.50 to 0.98, p = 0.037). Compared to the lowest tertile of aMED scores, participants in the highest tertile had a 37% reduced risk of GI cancers (OR 0.63, 95% CI 0.44 to 0.92, p = 0.014). RCS analysis indicated that both HEI-2020 and aMED scores were significantly associated with GI cancers; however, no significant non-linear relationship was observed. The primary findings confirm that higher adherence to HEI-2020 and aMED scores is associated with a lower risk of GI cancers. These results suggest that maintaining a high-quality diet may play a crucial role in the prevention and management of these cancers. Further research is needed to elucidate the mechanisms and effects of healthy diet management and high-quality diets in the prevention of GI cancers.